2017
DOI: 10.1177/1468087417730240
|View full text |Cite
|
Sign up to set email alerts
|

Diesel engine aftertreatment warm-up through early exhaust valve opening and internal exhaust gas recirculation during idle operation

Abstract: A large fraction of diesel engine tailpipe NOx emissions are emitted before the aftertreatment components reach effective operating temperatures. As a result, it is essential to develop technologies to accelerate initial aftertreatment system warm-up. This study investigates the use of early exhaust valve opening (EEVO) and its combination with negative valve overlap to achieve internal exhaust gas recirculation (iEGR), for aftertreatment thermal management, both at steady state loaded idle operation and over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…As a result, an increase in fueling is required during EEVO operation, enabling higher engine-out temperatures for improved “warm-up” performance. 13,16,20 LEVO and EEVO at high idle speeds will be shown to be capable of enabling emission-constrained, elevated engine-out temperatures and mass flows for improved aftertreatment “warm-up” performance.…”
Section: Motivation For Aftertreatment Tm High-speed Idle Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, an increase in fueling is required during EEVO operation, enabling higher engine-out temperatures for improved “warm-up” performance. 13,16,20 LEVO and EEVO at high idle speeds will be shown to be capable of enabling emission-constrained, elevated engine-out temperatures and mass flows for improved aftertreatment “warm-up” performance.…”
Section: Motivation For Aftertreatment Tm High-speed Idle Strategiesmentioning
confidence: 99%
“…Previous studies by several of the authors, and others, have demonstrated the ability to raise exhaust temperatures for more efficient aftertreatment thermal management (TM) by utilizing various strategies such as maximally closing a variable geometry turbine (VGT), cylinder deactivation (CDA), intake valve modulation, and exhaust valve modulation. 2,1017…”
Section: Introductionmentioning
confidence: 99%
“…Being a chemical system, the reaction rates are highly temperature dependent. 5 Where possible, avoidance of heavy duty diesel engines operating in city centre environments is to be encouraged. However, public buses, delivery vehicles and plant equipment are examples of where this is often impossible.…”
Section: Introductionmentioning
confidence: 99%
“…511 Previous studies have demonstrated the ability to raise exhaust temperatures by increasing the exhaust manifold pressure. 2,4,12,13…”
Section: Introductionmentioning
confidence: 99%